Paid Annual Leave and Working Hours - Warren, D; Wooden, M (My University, 2007)
Using data from wave 5 of the Household, Income and Labour Dynamics in Australia (HILDA) Survey, this study examines: (i) the extent to which Australian employees use their annual leave entitlements; and (ii) the association between annual leave taking and weekly hours of work. After restricting attention to employees likely to have entitlement to at least four weeks of paid annual leave, it is found that the mean number of days of leave taken per year is around 16 and that the majority (63%) take less than 20. The incidence of annual leave taking is found to vary positively correlated with the number of usual weekly hours of work, but the size of this effect is small and weak. It is concluded that persons who regularly report long hours of work each week are mostly not compensating by taking extended periods of leave each year, but neither is there evidence to support the hypothesis that the pressures at work that might lead many people to regularly work very long hours each week also cause them to forego their annual leave entitlements).
Melbourne Institute of Applied Economic and Social Research Working Paper Series
Keywords: Employment; Employment -- Conditions; Employment -- Hours; Labour market; Employment and unemployment